MAKING A VIDEO GAME - Higgins, Nadia (Mankato, Minnesota : Amicus and Amicus Ink, 2019)
"This book for elementary readers highlights the sequence of events from idea to a finished video game. Full-color photographs and a timeline support each step of the project's process, from planning gameplay and coding the prototype to designing and publishing the finished game. A glossary, further resources, and an index are included".
A new game idea! Planning it out t
Includes bibliographical references (page 31) and index.
Keywords: Video games -- Juvenile literature. -- Design; Video games -- Juvenile literature. -- Programming